2018
DOI: 10.1016/j.talanta.2018.06.084
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic techniques to detect ovarian cancer biomarkers in blood plasma

Abstract: Robust diagnosis of ovarian cancer is crucial to improve patient outcomes. The lack of a single and accurate diagnostic approach necessitates the advent of novel methods in the field. In the present study, two spectroscopic techniques, Raman and surface-enhanced Raman spectroscopy (SERS) using silver nanoparticles, have been employed to identify signatures linked to cancer in blood. Blood plasma samples were collected from 27 patients with ovarian cancer and 28 with benign gynecological conditions, the majorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 58 publications
1
40
1
Order By: Relevance
“…The presence of very low level of serum biomarkers in the early stage of the disease may be challenging in processing for clinical studies. Recently, for the first time, Raman spectroscopy has been used to assay the blood samples for diagnosis of early and late stage ovarian cancer (Paraskevaidi et al., 2018; Peng et al., 2014). Raman Spectroscopy is based on the phenomenon of inelastic light scattering caused when light interact with matter.…”
Section: Other Advanced Approaches For Early Diagnosis Of Ovarian Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of very low level of serum biomarkers in the early stage of the disease may be challenging in processing for clinical studies. Recently, for the first time, Raman spectroscopy has been used to assay the blood samples for diagnosis of early and late stage ovarian cancer (Paraskevaidi et al., 2018; Peng et al., 2014). Raman Spectroscopy is based on the phenomenon of inelastic light scattering caused when light interact with matter.…”
Section: Other Advanced Approaches For Early Diagnosis Of Ovarian Cancermentioning
confidence: 99%
“…In addition, to differentiate between healthy and ovarian cancer cases, the method was assessed in different levels of CA125 to rule out that the detection accuracy was due to CA125 level, and both techniques provided satisfactory results. Both techniques detected five spectral biomarkers, which are promising as multi-biomarker panel in diagnosing ovarian cancer (Paraskevaidi et al., 2018). These studies highlight the promising role of Raman spectroscopy in the biomarker studies and its adoption in multibiomarker studies will be prospective breakthrough in the field of biomarker research.…”
Section: Other Advanced Approaches For Early Diagnosis Of Ovarian Cancermentioning
confidence: 99%
“…These changes indicated that the contents of proteins, lipids, and other biological macromolecules in the serum of patients were significantly reduced, which may be related to the active growth and metabolism of malignant tumor cells and the rapid increase in the consumption of proteins, amino acids, and lipids, as similar results had been reported in literature on the detection of tumor serum by Raman spectroscopy. [8,[32][33][34] The peak intensities at 505 cm −1 (S S and proteins), 535 cm −1 (S S and proteins), 703 cm −1 (C S stretching and proteins), 1,032 cm −1 (CH 2 and CH 3 bending and phenylalanine), 1,313 cm −1 (CH 2 deformation and in-plane vibrations, tryptophan, α-helix, and phospholipids), and 1,342 cm −1 (CH 2 /CH 3 wagging, twisting and/or bending, α-helix proteins, and phospholipids) were higher in the LGG group and lower in the HGG group than in the control group, and the reasons for these results need to be investigated further. PCA-LDA has been performed in the classification of Raman spectroscopy in cancer diagnosis and has exhibited highly accurate prediction results.…”
Section: Discussionmentioning
confidence: 99%
“…Raman is a powerful technique for biological materials analysis, with applications ranging from cell imaging to cancer diagnosis [10][11][12]. Regarding ovarian cancer, Raman spectroscopy of tissue [13,14] as well as blood plasma and serum [15][16][17][18] has been reported. The main advantages of using biofluids rely in that sample preparation is not needed; hence, no reagents are required, and the liquid biopsies processing is less invasive than traditional tissue ones.…”
Section: Introductionmentioning
confidence: 99%